Dzielmy sie doświadczeniemPlatelet mapping in postoperative management of acute aortocoronary bypass thrombosis - Gwozdziewicz, Marek; Němec, Petr; Zezula, Radek; Novotny, Josef (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Platelet mapping has been introduced recently to help with the assessment of the antiplatelet drug therapy, which is necessary in patients who underwent coronary bypass surgery. A case of acute bypass thrombosis in the immediate postoperative period is presented, and the management of evolving myocardial ischemia is described. The efficacy of thromboelastography platelet mapping in appropriate postoperative antiplatelet therapy is highlighted.